2012
DOI: 10.5937/gads1247119t
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of morphological characteristics of two generations of football players

Abstract: SažetakDobro poznavanje antropoloških karakteristika sportista koji postižu vrhunske rezultate mogu biti orijentir i putokaz u kom pravcu treba usmeriti selekciju i trenažni proces. Različite sportske discipline određuju razvoj različitih antropoloških karakteristika, te bi za svaki sport trebalo definisati njihove standarde. Antropološke karakteristike su podložne vremenskim promenama, usled čega standardi imaju vremensku ograničenost.Cilj istraživanja je da se izvrši komparativna analiza morfoloških karakter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Furthermore, there were diverse opinions about the body composition and its effect on situational-motor abilities, where Ismaili et al [5] have presented greatest adverse, while Stanković et al [6] have showed the result maintained. Likewise, they should not disregard the fact that bone mass comprises 18-20% of the total, muscles comprise 50-53%, while fatty tissue mass is 8-10% in soccer players [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there were diverse opinions about the body composition and its effect on situational-motor abilities, where Ismaili et al [5] have presented greatest adverse, while Stanković et al [6] have showed the result maintained. Likewise, they should not disregard the fact that bone mass comprises 18-20% of the total, muscles comprise 50-53%, while fatty tissue mass is 8-10% in soccer players [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the first group comprises players with a somewhat lesser engagement in the game (the goalkeeper, two center defenders, and two forwards), while the second group includes players with more extensive game engagement (two wing backs and four midfielders). Based on the model of base motor domain structure, a hypothetical model of base motor abilities for specific groups of player positions has been defined, including a selection of base motor tests for their assessment [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation